Identification of novel mutations in the carbohydrate sulfotransferase gene (CHST6) causing macular corneal dystrophy. - El-Ashry, M; El-Aziz, A; Wilkins, S; Cheetham, M; Wilkie, SE; Hardcastle, A; Halford, S; Bayoumi, A; Ficker, L; Tuft, S; Bhattacharya, S; Ebenezer, N (2002)
PURPOSE: Macular corneal dystrophy (MCD) is a rare corneal dystrophy that is characterized by abnormal deposits in the corneal stroma, keratocytes, Descemet's membrane, and endothelium, accompanied by progressive clouding. It has been classified into three immunophenotypes--MCD types I, IA, and II--according to the serum level of sulfated keratan sulfate (KS) and immunoreactivity of the corneal tissue. Recently, mutations in a new carbohydrate sulfotransferase gene (CHST6) encoding corneal glucosamine N-acetyl-6-sulfotransferase (C-GlcNac-6-ST) have been identified as the cause of MCD. Mutation screening of the CHST6 gene has been undertaken to identify the underlying mutations in five unrelated British families with MCD. METHODS: DNA was extracted from venous blood obtained from all participants, and the coding region of CHST6 was amplified by polymerase chain reaction (PCR). The PCR products were analyzed by direct sequencing and restriction enzyme digestion. Enzyme-linked immunosorbent assay (ELISA) was performed to assess the presence of KS in serum from the probands of MCD-affected families participating in the study. RESULTS: Six novel missense mutations--four homozygous and two compound heterozygous--were identified in the CHST6 gene. The ELISA showed that the disease in all patients participating in the study was of MCD type I, including the subtype IA. CONCLUSIONS: These novel mutations are thought to result in loss of corneal sulfotransferase function, which would account for the MCD phenotype.